Impact of the Great Recession on Industry Unemployment: A 1976-2011 Comparison - Yelena F. Takhtamanova; Eva Sierminska (Institute for the Study of Labor (IZA), 2016)
This paper studies the mechanisms driving the persistently high unemployment rate during the last recession and mild recovery. Previous studies have examined the demographic aspect of the recession. We focus on specific industries. Consequently, we propose a methodology to decompose changes in the unemployment rate into worker inflows and outflows across industry groups and outline the unique characteristics of the latest recession (including examining cyclical and structural forces). We use harmonized- reclassified industry data for 1976-2011 in the United States, which allows us to make comparisons previously not possible.
Keywords: J1; J6; 330; unemployment; worker flows; job finding rate; separation rate; industry